ANALISIS KETERKAITAN MEDIA SOSIAL, MORD OF MOUTH, POTENSI WISATA, DAN PRAKTIK PLACE BRANDING DI TAMAN NASIONAL KARIMUNJAWA, JAWA TENGAH - Yordi Hikmawan; Ari Pradhanawati (Universitas Diponegoro, 2016)
Public interest to tourism activity is always increasing, seen from the many deals offered by Travel Agencies in internet. Tourism spots seem to be a promising business to by playing the tourism management role. Karimunjawa Island has massive potentials that need to be exposed to public. The paper seeks to provide insights into the application of marketing communication strategies, with social media and word of mouth communication in tourism industry from the perspectives of its tourism potentials, evaluating their effectiveness for place branding management at Karimunjawa National Park. The specific purpose is to uncover the important role marketing communication with practice of social media and word of mouth to build the place brands by engaging potential visitors. The social media and word of mouth proved to be a major communication vehicle that spread across the region like wildfire. Tourism industry is one of the sectors that have beneficiated the most from the marketing communication strategies. As a result social media word of mouth have become an integral part of Karimunjawa National Park place branding.Qualitative case-study method generates understanding of how social media and word of mouth communicate the Karimunjawa National Park’s tourism potentials. In-depth interview allows exploration of how the marketing communication strategies with practice of social media and word of mouth used in place branding processes. As a result, the relationship between travel agent and customers is closer than ever, with businesses continuing to turn to social media and word of mouth to promote their services and reach customers in a more intimate and personal way.